KOMPETENSI GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN DI PAUD CAHAYA DESA KAPUR KECAMATAN SUNGAI RAYA - Munawaroh, Siti; Syukri, M; R, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The aim of this research is to know the ability of teacher to arrange the learning devices in paud cahata desa kapur kecamatan sungai raya kabupaten kubu raya. The learning devices consisted of the ability of teacher in prepared the annual programs, prepared the semester programs, prepared weekly programs and prepared the lesson plan. this research used qualitative approach and descriptive method. The subject of this research is the teacher of paud cahaya. The result of this research showed that annual programs and semester programs are prepared by the headmaster of the paud not the teacher, while the weekly programs and lesson plan are prepared by the teacher. Regarding to the result of this research, the researcher suggested that the teacher should adding more knowledge of how to prepared annual programs and the lesson plan. The cooperation between the teachers should always be maintained. Participating in training seminars to make learning tools to further deepen the ability of teachers to develop learning tools. Keyword : Teacher Competency, Compile,Learning Media